A STUDY ON DIET AND RELATIONSHIP OF INDUS VALLEY SPINY-TAILED LIZARD - ( S aara hardwickii) W ITH VEGETATION S. Qasim; M. Rais; F. Akrim; T. Mahmood (Journal of Animal and Plant Sciences, 2018)
The Spiny-tailed Lizard (Saara hardwickii) is widely recognized as a herbivore lizard inhabiting arid areas, but less is known about association of the lizard abundance with different vegetation type and lizards diet using stomach content flushing method. We conducted the present study to see relationship of woody and non-woody vegetation with abundance of Spiny-tailed Lizard in Chakwal District, Punjab, Pakistan, and to see if proportions of food item species were similar in the samples of stomach contents and fecal samples. We found a weak significant relationship with woody vegetation cover (trees and shrubs) but relatively strong significant relationship with non-woody vegetation cover ( herbs and grasses). Herbs such as Chenopodium album and Peganum hermala accounted for most of the volume and frequency in stomach content and fecal samples followed by grasses Cynodon dactylon and Desmostachya bipinnata. We found significant difference in the number of food item species recorded from the samples of stomach contents and fecal samples. We recorded Acacia modesta ( tree) and Eruca sativa ( herb) only from samples of stomach contents while Ziziphus nummularia (shrub) and Cymbopogon jwarancusa (grass) only from the fecal samples whereas the other food item species were the same. Of all the food items, only the proportion of Peganum hermala (herb) in the stomach content samples and fecal samples were different. We concluded that the lizard abundance was more related with non-woody vegetation than woody vegetation. The lizard did not selectively forage on the vegetation rather it fed on herbs and grasses common in its habitat and might have ingested insects incidentally. The stomach content flushing method is less tedious and yield similar result as that of a more robust fecal pellet analysis method. On contrary, fecal pellet analysis is relatively harmless while flushing the stomach contents may put the lizard under stress. Cembranos, 2015; Baeckens, 2017; Perez-Cembranos et
Keywords: Uromastidae; Stomach content flushing; Fecal pellet analysis; linear regression; Cynodon dactylon.